Creating and integrating a new patient experience leadership role: A consultative approach for partnering with executive and clinical leaders - Denise Kennedy (The Beryl Institute, 2015)
Many healthcare organizations are creating new leadership roles to add subject matter expertise and structure to their patient experience improvement efforts. The patient experience field is emerging, however, so there are many questions about this role’s function and how best to structure it in the organization for maximal effectiveness. This article explores the benefits of a consultative approach for improving the patient experience. Previous research on management consulting and the integration of new roles in established organizations is briefly reviewed. Mayo Clinic Arizona’s (MCA) comprehensive, "7-prong" service model is revisited. Developed and implemented in 2008, the model is predicated on consultative relationships with executive and clinical leaders, is driven by data and accountability, and has demonstrated efficacy in improving the patient experience in specialty and primary care settings. Seven widely accepted service quality principles comprise the model: (1) multiple data sources to drive improvement; (2) accountability for service quality; (3) service consultation and improvement tools; (4) service values and behaviors; (5) education and training; (6) ongoing monitoring and control; and (7) recognition and reward. The focus of this article is Prong 3, service consultation. MCA’s consultative approach to structuring the patient experience leader is discussed, responsibilities are defined, qualifications are suggested, and key affiliations for integrating this new leadership role are proposed.